Effects of Integrative Neuromuscular Training Combined With Regular Tennis Training Program on Sprint and Change of Direction of Children - Wang, Zhi-Hai; Pan, Rui-Cheng; Huang, Meng-Ru; Wang, Dan (Frontiers in Physiology, 2022)
Objective: The aim of this study was to investigate the effects of integrative neuromuscular training (NMT) on sprint and the ability to change direction for children who are between the ages of 7 and 8 and beginning to play tennis. Methods: Thirty-two participants were randomized into a training group (TG; n = 16) and a control group (CG; n = 16). All participants attended tennis classes twice a week for a continuous eight weeks. In addition, the TG received NMT (e.g., 20-m sprints, running at four corners, rope ladder drills, etc.), which progressed in difficulty every two weeks. Pre-intervention and post-intervention measurements, including a 30-meter sprint test, a 5–10–5 test, and a 3 × 10 meter shuttle run test, were assessed by a Smartspeed laser timing gate system, while the spider agility test was evaluated with a stopwatch. Results: Two-way repeated measures ANOVA found significant differences in the interaction between time and group among variables measured. Results were as follows: time in the 30 m sprint (F = 13.467, 95% CI = 7.163 - 7.506, p = 0.001, η2p = 0.310, Δ = 0.42 s); 5–10–5 test (F = 13.975, 95% CI = 8.696 - 9.017, p = 0.001, η2p = 0.318, Δ = 0.78 s); 3 × 10 m shuttle run (F = 7.605, 95% CI = 11.213 - 11.642, p = 0.01, η2p = 0.202, Δ = 0.77 s); and spider agility test (F = 34.555, 95% CI = 28.258 - 29.670, p ＜ 0.001, η2p = 0.535, Δ = 3.96 s). The results demonstrated a greater decrease in sprint and change of direction (COD) time among the TG than the CG from pre-intervention to post-intervention. Conclusion: A regular tennis training combined with NMT program could produce greater improvement in a player’s sprint and ability to change direction when introduced to childhood tennis beginners in a sensitive period, compared to tennis class intervention only.